Reação de cultivares e controle da antracnose em soja - Souza, Rosemari Terezinha de (2010)
Anthracnose is one of the most important diseases of soybeans in warm and rainy regions of Brazil. In the South, the disease occurs in rainy summers, although the causal agent is recovered every year from assymptomatic plant tissues. Anthracnose can occur from seedling emergence to adult plant stages and its field management has been limited by cultivars susceptibility and low efficacy of fungicide spray programs. Such factors led to this study, which comprises evaluations of cultivar reaction, sensibility of Colletotrichum truncatum to fungicides, and performance of fungicides in both preventive and curative applications, as well as in field conditions. The experiments were carried out at the Universidade de Passo Fundo, from 2005 to 2008. Disease incidence and cultivar susceptibility were higher as plants were inoculated at younger stages. At V1-V2, for example, all cultivars (Caiapônia, BRS 154 RR, BRS 242 RR, BRS 244 RR, CD 212 RR, CD 213 RR, CD 214 RR, CD 215 RR, CD 219 RR, CD 245 RR, Fundacep 35, Fundacep 53 RR, Mireia RR, AG 6001 RR, AG 6445 RR, and AG 8000 RR) were susceptible, especially in early growth stages. The fungicide concentration needed to inhibit in vitro fungal growth by 50% was 1.05 mg.L-1 to epoxyconazol + pyraclostrobin, 2.6 mg.L-1 to cyproconazol + trifloxystrobin, 4.95 mg.L-1 to tebuconazol, 9.9 mg.L-1 to cyproconazol + trifloxystrobin, and 100 mg.L-1 to carbendazim. Prevenctive sprays of the same fungicides protected plants for 12 days after application. Curative control of disease latent infections was possible up to five or six days after inoculation and varied between cultivars. Field spray programs with two applications of the fungicides carbendazin, tebuconazol, ciproconazol + azoxystrobin, cyproconazol + trifloxystrobin, or epoxiconazol + pyraclostrobin reduced disease incidence on pods by less than 50%, but resulted in increased grain yields over non-treated plots. Disease control and grain yield were better when spray programs initiated at R1 instead R2. Because most soybean cultivars are very susceptible to anthracnose and chemical control is only partially efficacious after disease establishment into plants, other control strategies such as crop rotation and use of treated seeds are highly recommended